2023
DOI: 10.3390/cancers15030594
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Survivors and Healthy Women: Could Gut Microbiota Make a Difference?—“BiotaCancerSurvivors”: A Case-Control Study

Abstract: In this first analysis, samples from 23 BC survivors (group 1) and 291 healthy female controls (group 2) were characterised through the V3 and V4 regions that encode the “16S rRNA” gene of each bacteria. The samples were sequenced by next-generation sequencing (NGS), and the taxonomy was identified by resorting to Kraken2 and improved with Bracken, using a curated database called ‘GutHealth_DB’. The α and β-diversity analyses were used to determine the richness and evenness of the gut microbiota. A non-paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…The abnormal intestinal development in PJS patients may be related to the effects of intestinal metabolic changes on the brain-intestinal axis and intestinal mucosal epithelium. Similar metabolic abnormalities have been found in patients with ulcerative colitis, colon cancer, and breast cancer [ 65 68 ]. The above studies suggest that there is a potential association between differences in metabolic pathways and PJS.…”
Section: Discussionsupporting
confidence: 72%
“…The abnormal intestinal development in PJS patients may be related to the effects of intestinal metabolic changes on the brain-intestinal axis and intestinal mucosal epithelium. Similar metabolic abnormalities have been found in patients with ulcerative colitis, colon cancer, and breast cancer [ 65 68 ]. The above studies suggest that there is a potential association between differences in metabolic pathways and PJS.…”
Section: Discussionsupporting
confidence: 72%
“…The study conducted by Bobin-Dubigeon et al [ 41 ] demonstrated a reduction in gut microbiota diversity, a relative enrichment in Firmicutes , and a depletion in Bacteroidetes among patients with breast cancer as compared to those of healthy women. In another controlled study, patients with breast cancer exhibited a lower abundance of some microbial taxa, including Bacteroidetes phylum , Firmicutes phylum , Verrucomicrobia phylum , Clostridium genus , Shigella genus , Bifidobacterium genus , Akkermansia muciniphila , Clostridium perfringens , Escherichia coli , Bacteroides uniformis , Clostridium hathewayi , and Faecalibacterium prausnitzii [ 42 ].…”
Section: Changes Of Gut Microbiota In Patientsmentioning
confidence: 99%
“…It has been observed that the composition of the gut and mammary microbiota may differ between patients diagnosed with breast cancer and healthy subjects due to a disruption in the balance of this commensal community (Table 4). This imbalance would result in an altered or dysbiotic state in the microbiota that could be implicated in the etiology of cancer, influencing the disease's prevention, diagnosis, and prognosis [6,12,13,22]. ↑ abundance of Veillonellaceae and Dialister in patients scheduled for systematic adjuvant treatment.…”
Section: Main Outcomesmentioning
confidence: 99%